Women's engagement, views and experiences of postnatal follow-up after gestational diabetes mellitus in pregnancy. (October 2021) - Roberts, Siân Pierce; Brown, Sheila JS; Roberts, Seren Haf
Abstract: Background: The evidence base relating to women's engagement and experiences of postnatal care following Gestational Diabetes Mellitus in the United Kingdom is limited. Additionally, the uptake of a postnatal fasting blood glucose testing following Gestational Diabetes Mellitus appears to be poor. Objective: This study aimed to explore women's engagement, views and experiences of postnatal care following Gestational Diabetes Mellitus in the United Kingdom. Design and Participants: An online survey of participants that had Gestational Diabetes Mellitus was undertaken to gather mixed-methods data regarding women's engagement, views and experiences of postnatal care. Demographic data were also collected. Findings: A total of 31 participants completed the online survey; respondents were from two countries in the United Kingdom only (England and Wales). Some respondents indicated positive postnatal experiences following Gestational Diabetes Mellitus (such as good family support) with effective communication by some healthcare teams and screening coinciding with engagement with the routine six week follow-up appointment. Overall, findings indicated a general dissatisfaction with the care provided, mostly due to the inconsistency of information and advice in relation to the type of screening test and the timing, location and organisation of blood glucose screening and follow up care. Conclusion: This study provides an insight into ways that may improve women's engagement, views and experiences of postnatal care following Gestational Diabetes Mellitus in England and Wales. Implications for practice: Findings indicate a lack of consistent adherence to national guidance. A clear care pathway facilitating continuity of care for women in the postnatal period following Gestational Diabetes Mellitus, along with further education and support for health professionals, may improve the provision of postnatal care. The authors recognise the limitations of this small standalone study however, findings highlight the need for further exploration of postnatal follow up following Gestational Diabetes Mellitus in the UK.